Maternal and fetal outcomes of obese pregnant women: a prospective cohort study - John, Jenniferbritto; Mahendran, Mary (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Obesity in Indian women had increased from 10.6% to 14.8% in India. Mothers who are overweight or obese during pregnancy and childbirth cause significant antenatal, intrapartum, postpartum and also neonatal complications. The present study aimed to explore various maternal and fetal outcomes influenced by maternal obesity. The objective was to find the effect of obesity on maternal and perinatal outcome among obese pregnant women compared to those of normal weight. Methods: The study was conducted in antenatal women attending antenatal outpatient department of CSI rainy multispecialty hospital located in North Chennai of South India. Consecutive sampling method was followed to include 50 cases and 50 controls. Analysis was done with IBM SPSS v.21.0. Chi square test was applied to find difference between proportions. For comparison of means independent t-test and ANOVA was applied. Pearson's correlation was done to find association between maternal BMI and birth weight. Results: Sixteen (32%) cases developed gestational diabetes mellitus during their antenatal period and 19 (38%) developed gestational hypertension. 10% underwent in emergency caesarean section and in 28% cases elective caesarean section was done. The proportion of cases who developed ante partum complications including gestational diabetes mellitus, gestational hypertension and preeclampsia were higher than in control groups (p value = 0.03,0.00,0.004 respectively). The need for induction of labour and caesarean section was found to be higher in cases than in controls (p = 0.014,0.03 respectively). Increased NICU admissions for stabilization of the newborn among cases was higher than control group (p = 0.012). Conclusions: It was clearly evident from the present study that maternal obesity had adverse maternal and fetal outcomes. Maternal obesity was strongly associated with antenatal complications like gestational diabetes mellitus, gestational hypertension, preeclampsia and increase in need for induction of labour and operative interference.